Basic mechanisms and regulation of fibrinolysis. (June 2015) - Longstaff, C.; Kolev, K.
Summary: Fibrinolysis appears in many diverse physiological situations, and the components of the system are well established, along with mechanistic details for the individual reactions and some high‐resolution structures. Key questions in understanding the regulation of fibrinolysis surround mechanisms of initiation and propagation, the localization of fibrinolysis reactions to the fibrin clot, and the influence of fibrin structure and clot composition on thrombolysis. This review covers these key areas with a focus on recent developments on fibrin structure and binding, the effects of a variety of cell types, the consequences of histones and DNA released by neutrophils, and the influence of flow. A complete understanding of the regulation of fibrinolysis will come from the building of detailed mathematical models. Suitable models are at an early stage of development, but may improve as model clots increase in complexity to incorporate the components and interactions listed above.